Comparison of Radical Scavenging Capacity of Different Extracts of Barks and Needles of Pinus roxburghii and Pinus wallichiana - Maimoona, Alya; Naeem, Ismat; Shujaat, Shahida; Saddiqe, Zeb; Mughal, Tahira; Mehmood, Talib (Asian Journal of Chemistry, 2010)
In this paper, the comparative study of antioxidant activities exhibited by different extracts of bark and niddles of Pinus roxburghii and Pinus wallichiana were evaluated. Polar and nonpolar extracts were obtained by fractionating the crude methanolic extracts of bark and needles of each plants with n-hexane, dichloromethane, ethylacetate and butanol, respectively leaving aqueous fractions behind. Activity of each sample was evaluatd using 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging assay. The total phenolic and total flavonid contents of each sample were assessed. Correlation between DPPH scavenging potential (IC50) and total phenolic content is not so strong and is found to be positive only in case of PrB (r2 = 0.3602) fractions while correlation between scavenging percentage and total flavonoids is positive in PrN, PwN and PrB fractions. However, fractions exhibiting best antioxidant potential are rich in both flavonoids and phenolics and these fractions are polar i.e. ethyl acetate, butanol and water fractions.